2021
DOI: 10.3389/fcimb.2021.732423
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exogenous Sex Steroids on the Vaginal Microbiota: A Systematic Review

Abstract: BackgroundExogenous sex steroids within hormonal contraception and menopausal hormone therapy (MHT) have been used for family planning and management of menopausal symptoms, without consideration of their effects on the vaginal microbiota. This is largely because their use predates our understanding of the importance of the vaginal microbiome on human health. We conducted a systematic review (PROSPERO: CRD42018107730) to determine the influence of exogenous sex steroids, stratified by oestrogen-containing or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 80 publications
(264 reference statements)
1
9
0
Order By: Relevance
“…Our results for COCs are consistent with multiple studies that demonstrated a reduced risk of incident and prevalent BV among those using combined estrogen and progestin contraceptive methods. 29 , 30 , 31 , 64 , 65 Our results are also similar to other studies evaluating the effect of COCs on the composition of the vaginal microbiota characterized using molecular approaches (16S rRNA gene amplicon sequencing or qPCR), including a cross-sectional study (N = 682) comparing the vaginal microbiota of women on HC to those who used condoms for contraception. 34 That study found that those using COCs (N = 206) were more likely to be colonized by Lactobacillus spp.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results for COCs are consistent with multiple studies that demonstrated a reduced risk of incident and prevalent BV among those using combined estrogen and progestin contraceptive methods. 29 , 30 , 31 , 64 , 65 Our results are also similar to other studies evaluating the effect of COCs on the composition of the vaginal microbiota characterized using molecular approaches (16S rRNA gene amplicon sequencing or qPCR), including a cross-sectional study (N = 682) comparing the vaginal microbiota of women on HC to those who used condoms for contraception. 34 That study found that those using COCs (N = 206) were more likely to be colonized by Lactobacillus spp.…”
Section: Discussionsupporting
confidence: 87%
“… 41 To further corroborate this, a recent systematic review found that estrogen containing compounds overall seemed to promote an optimal vaginal microbiota, but the effect of progestin only contraceptives was much less clear, with some concerns for potential negative effects. 65 In our study, when participants using all forms of HC were included, the results did not change, participants remained more likely to be stable and more likely to be dominated by Lactobacillus spp. if they were using HC.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The vaginal pH and Lactobacilli levels were restored to premenopausal levels in patients who underwent hormone therapy, though no significant changes were observed in the other groups [ 39 ]. In a systematic review of four clinical trials investigating the effects of percutaneous estrogen administration on the vaginal microbiome in postmenopausal women, Ratten et al [ 40 ] found that topical estrogen administration increases vaginal Lactobacillus . In a randomized, double-blind, placebo-controlled study conducted by Petricevic et al, when probiotic capsules containing L. rhamnosus GR-1 and L. reuteri RC-14 were administered daily for 14 days, there was a significant improvement in the Nugent score compared with that in the placebo group.…”
Section: Changes In Vaginal Microbiota In Menopausal Womenmentioning
confidence: 99%
“…Estrogens have multiple physiological effects such as on metabolism, menstruation, coagulation, bone health, the cardiovascular system ( 1 ) and the vaginal microbiome ( 2 ), and are also associated with adverse effects such as increasing susceptibility to candida albicans infection ( 3 , 4 ). In addition, sex steroid hormones have important neuropsychological and behavioral effects.…”
Section: Introductionmentioning
confidence: 99%